Reliability of surface electromyography activity of gluteal and hamstring muscles during sub-maximal and maximal voluntary isometric contractions. (April 2018) - Bussey, Melanie D.; Aldabe, Daniela; Adhia, Divya; Mani, Ramakrishnan
Abstract: Background: Normalizing to a reference signal is essential when analysing and comparing electromyography signals across or within individuals. However, studies have shown that MVC testing may not be as reliable in persons with acute and chronic pain. Objectives: The purpose of this study was to compare the test-retest reliability of the muscle activity in the biceps femoris and gluteus maximus between a novel sub-MVC and standard MVC protocols. Methods: This study utilized a single individual repeated measures design with 12 participants performing multiple trials of both the sub-MVC and MVC tasks on two separate days. The participant position in the prone leg raise task was standardised with an ultrasonic sensor to improve task precession between trials/days. Day-to-day and trial-to-trial reliability of the maximal muscle activity was examined using ICC and SEM. Findings: Day-to-day and trial-to-trial reliability of the EMG activity in the BF and GM were high (0.70–0.89) to very high (≥0.90) for both test procedures. %SEM was <5–10% for both tests on a given day but higher in the day-to-day comparisons. The lower amplitude of the sub-MVC is a likely contributor to increased %SEM (8–13%) in the day-to-day comparison. Conclusions: The findings show that the sub-MVC modified prone double leg raise results in GM and BF EMG measures similar in reliability and precision to the standard MVC tasks. Therefore, the modified prone double leg raise may be a useful substitute for traditional MVC testing for normalizing EMG signals of the BF and GM. Highlights: Reliability of EMG activity was high to very high for both MVC and Sub-MVC tasks. Measurement error was highest between days and lowest between trials. Modified prone double leg raise results in reliable EMG measures. The prone double leg raise is an acceptable alternative to MVC testing.